A physiologically based pharmacokinetic model of vitamin D. Issue 12 (6th June 2017) - Sawyer, Megan E.; Tran, Hien T.; Evans, Marina V.
Abstract: Despite the plethora of studies discussing the benefits of vitamin D on physiological functioning, few mathematical models of vitamin D predict the response of the body on low‐concentration supplementation of vitamin D under sunlight‐restricted conditions. This study developed a physiologically based pharmacokinetic (PBPK) model utilizing published human data on the metabolic cascade of orally derived, low‐concentration (placebo, 5 μg and 10 μg) supplementation of vitamin D over the course of 28 days in the absence of sunlight. Vitamin D and its metabolites are highly lipophilic and binding assays of these compounds in serum may not account for binding by lipids and additional proteins. To compensate for the additional bound amounts, this study allowed the effective adipose–plasma partition coefficient to vary dynamically with the concentration of each compound in serum utilizing the Hill equation for binding. Through incorporating the optimized parameters with the adipose partition coefficient adaptation to the PBPK model, this study was able to fit serum concentration data for circulating vitamin D at all three supplementation concentrations within confidence intervals of the data. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : This study developed a PBPK model utilizing published human data on the metabolic cascade of orally‐derived, low‐concentration supplementation of vitamin D under sunlight‐restricted conditions. In addition, this study allowed the effective adipose:plasma partition coefficient to vary with serum concentration, allowing for a fit to serum concentration data at all supplementation levels.